What makes public sector innovations survive?: an exploratory study of the influence of feedback, accountability and learning - Acker, Wouter van; Bouckaert, Geert (2018)
The question whether public sector innovations last, and what determines their chances of survival, remains a gap in the public management literature. This exploratory study focuses on the winners and nominees of public sector innovation awards in Belgium, France, the Netherlands, Romania, Slovakia and the UK. Through a survey covering 220 cases, it examines whether feedback loops, accountability mechanisms and learning processes (FAL) can explain the survival of public sector innovations. The conclusion is that a culture of feedback, accountability and learning seems to be positively linked with the survival of innovations. - Reproduced.
Keywords: Accountability; Government enterprise; Innovation; Public administration; Public sector